Effects of Home Care on the Use of Medical Services by the Elderly in China’s National Medical Insurance System - Qin, Wenshuai; Chen, Chien‐Ping; Wang, Yangyang; Chen, Hong; Zhang, Ze; Qin, Lijian (International Advances in Economic Research, 2025)
Keywords: Ambulatory care; Elderly; Government (linguistics); Health care; Home care; Medical care; Medical insurance; Medical record; Medical services; Restructuring; Service (business); Social security; dept.bus

Exploring the relationship between principal mentoring, teacher assessment, and principal engagement - Gantasala, Venugopal; Gantasala, Swapna; Hakouz, Abeer; Gantasala, Sai (Mentoring & Tutoring Partnership in Learning, 2025)
Keywords: Context effect; Perception; Principal (computer security); Principal component analysis; Principals’ mentoring; Statistical analysis; Student engagement; dept.bus; principals’ engagement; teacher assessment

Influence of performance feedback and academic performance on parent–family involvement and parent satisfaction in US schools - Venugopal Prabhakar, G.; Swapna Bhargavi, G.; Ramesh Reddy, P.; Shehab, M. (Journal of Community Psychology, 2023)
Parental and family involvement in schools has been a concern for educators and administrators. The authors set out to assess the path directions and significance of the interrelationships between Performance Feedback (PF), Academic Performance (AP) on Parent–Family Involvement (PFI), and Parent Satisfaction (PS) in schools. This study utilizes data from the PFI in Education Survey 2019 under the National Household Education Surveys program done by the US Department of Education. The sample for this research is 954 parents. Structural equation modeling was employed using AMOS. Results establish the three research propositions: influence of PFI on PS with the mediation of AP and PF, influence of AP on PS is moderated by PF, influence of AP on PFI is moderated by PF. The findings are important for school administrators and all stakeholders for ensuring greater PFI, improved PF and AP of students, and higher PS. This study is unique in assessing the interactional effects of the variables considered. The study also establishes mediating and moderating influences and offers new insights in understanding the influences on PFI and PS and some bidirectional effects. © 2023 Wiley Periodicals LLC.
Keywords: academic performance; dept.bus; parent satisfaction; parent–family involvement; peer-reviewed; performance feedback

The nature of entrepreneurial orientation strength: the impact of shared values on firm performance - Weinzimmer, Laurence G.; Michel, Eric J.; Robin, Jennifer (Journal of Management & Organization, 2021)
Drawing on Wales, Monsen, and McKelvie's (2011, Entrepreneurship Theory and Practice, 35(5), 895–923) model of entrepreneurial orientation pervasiveness and the strong culture hypothesis (Denison, 1984, Organization Dynamics, 13, 4–22), this study investigates how entrepreneurial orientation (EO) strength, defined as the level of agreement in the shared perceptions of EO, serves as a boundary condition of the EO–firm performance relationship. Four field studies provide evidence for a valid and reliable 10-item multidimensional measure of entrepreneurial orientation, the EO-10, which in turn, may be used to assess EO strength. We establish content and construct validity of the EO-10 (study 1; n = 447 employees), criterion-related validity with revenue growth and sales growth (study 2; n = 412 employees in 43 profit centers), and convergent validity with Covin and Slevin's (1989, Strategic Management Journal, 10, 75–87) 9-item measure (study 3; n = 291 employees). Finally, in study 4 (n = 853 employees nested in 22 organizations), we demonstrate the interactive effects of EO and EO strength on profit growth and revenue growth. In sum, this study provides conceptual and empirical evidence for the importance of EO strength as a moderator of the EO–firm performance relationship.
Keywords: Culture; dept.bus; entrepreneurial orientation strength; firm performance; peer-reviewed; scale development